Nitrogen Supply Regulates Vascular Bundle Structure and Matter Transport Characteristics of Spring Maize Under High Plant Density - Ren, Hong; Jiang, Ying; Zhao, Ming; Qi, Hua; Li, Congfeng (Frontiers in Plant Science, 2021)
Nitrogen (N) fertilizer application greatly enhances grain yield by improving dry matter accumulation and grain filling in spring maize. However, how N application rates regulate the vascular bundle structure, matter transport and grain filling of spring maize under a high planting density has been poorly understood thus far. In this study, we analysed the relationship between grain filling, vascular bundle structure and matter transport efficiency of spring maize in the field. Zhongdan909 (ZD909) was used as the experimental material in a 2-year field experiment from 2015 to 2016, and it was grown under different N levels (0, 150, and 300 kg N ha-1) applied to the grain-filling stage of plots with planting densities of 67,500 plants ha-1 (ND) and 90,000 plants ha-1 (HD). Nitrogen application significantly optimized the structure of the big and small vascular bundles. In particular, there was an increase in the total number of small vascular bundles in the peduncle and cob of the ear system, i.e., increases of 51.8% and 25.7%, respectively, and the proportions of small vascular bundles to the total number of vascular bundles in the peduncle and cob were significantly increased. The root bleeding sap and matter transport efficiency (MTE) of maize were significantly increased by N application under both ND and HD, as indicated by the significant increase in the rate of 13C-photosynthate allocation to grain and amount of postsilking dry matter at maturity. Moreover, N application greatly improved the mean grain-filling rate (Gmean) under ND and HD by 30.0% and 36.1%, respectively, and the grain-filling rate increased, leading to a distinct improvement in the grain sink at the grain-filling stage. We concluded that nitrogen application significantly optimized the vascular bundle structure of the ear system, increased the matter transport efficiency and improved photosynthate distribution to the grain, ultimately enhancing the filling rate and grain yield.